2016
DOI: 10.1177/1557988316681667
|View full text |Cite
|
Sign up to set email alerts
|

Males’ Ability to Report Their Partner’s Contraceptive Use at Last Sex in a Nationally Representative Sample: Implications for Unintended Pregnancy Prevention Evaluations

Abstract: Addressing and enabling the role of males in contraceptive choices may facilitate efforts to reduce unintended pregnancy rates and disparities in the United States, but little is known about males’ ability to report their partners’ contraceptive use. Data from the 2011-2013 National Survey of Family Growth from 2,238 males aged 15 to 44 years who had vaginal sex with a noncohabiting or nonmarital partner and were not seeking pregnancy were examined to tabulate the proportion of males able to report whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…In contrast, for unintended pregnancy, having both fewer and more partners was associated with lower odds compared to having 4–7 partners. One explanation for this may be that the Early/Atypical Initiators group is comprised of more men who could be unaware of a partner’s contraceptive use or pregnancy status, especially in newer partnerships (Garbers et al, 2017; Rendall, Clarke, Peters, Ranjit, & Verropoulou, 1999). Similarly, males with more sexual partners may be less likely to know about a former partner’s pregnancy status.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for unintended pregnancy, having both fewer and more partners was associated with lower odds compared to having 4–7 partners. One explanation for this may be that the Early/Atypical Initiators group is comprised of more men who could be unaware of a partner’s contraceptive use or pregnancy status, especially in newer partnerships (Garbers et al, 2017; Rendall, Clarke, Peters, Ranjit, & Verropoulou, 1999). Similarly, males with more sexual partners may be less likely to know about a former partner’s pregnancy status.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Extensive research has been conducted on the role of females and males in reproductive health decision-making, especially among teen populations. [610] Several studies have shown that increasing students’ sense of contraceptive responsibility to protect sexual partners may help reduce the high rate of unplanned pregnancies among students. [11,12]…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa, men may rely on one partner to use a female method, while using condoms with a second, and no method with a third (7). This is also representative of the difference in contraceptive-use reporting between men and women and there is evidence which shows that men tend to over-report contraceptive use and provide socially desirable answers (45,73).…”
Section: Men Look At Maintaining Sexual Frequencymentioning
confidence: 80%